Cartografia do trabalho de agentes penitenciários: reflexão sobre o “dispositivo prisão” - Figueiró, Rafael de Albuquerque (2015)
The Brazilian prison system is going through a serious crisis, not only due to the growth in the number of prisoners and the consequent overcrowding of prisons, but also for the violation of human rights, institutionalization and difficulty in social rehabilitation of inmates. Furthermore, the harmful effects of the prison system affect their workers, who generally are not prioritized by researchers, health programs and government policies. The literature pointing to some consequences of work in prison, among them, the mental illness, stress, alcohol abuse, etc., but little is known about this profession, their problems, the difficulties of their work routine, so as subjective processes involved. So, what are the effects of this work in the prison in the lives of correctional officers? What strategies developed to address the work in prison? This research aims to analyze the effects of this work in the prison in the lives of correctional officers from the state prison in Parnamirim, located in the metropolitan region of Natal-RN. Within the theoretical and methodological perspective of institutional analysis and cartography were carried conversation circles, interviews, in addition to participant observation of the correctional officers work’s routine. The results point to a working routine marked by the performance of procedures that involve risk to the worker, generating situations of tension and stress. Besides, the culture of violence (which is implemented in jail everyday) as well as the training and initial learning of the profession, are responsible for the militarization process of the subjectivities of the correctional officers, producing hard subject, disciplined, stiff, likely to violent practices and other rights violations. Other mapped effects relate to the acquisition of knowledge about the human (“psy” knowledge) responsible for forging the conception of the criminal as "dangerous subject", which, in turn, acts as subjectivity vector in the daily life of prison guards by setting up a way of life crossed by fear and insecurity outside the work environment. Produces a control in the open about their lives and their families, limiting them with regard to family and community life and the realization of leisure activities in public spaces. In this sense, it appears that the arrest acts producing “bad meetings” (from Espinosa's perspective), once it produces sad affections responsible for weakening the conatus, limiting the possibilities of action of these subjects. Although agents develop some strategies to deal with the difficulties of working in prison (among which stand out the development of other professional or leisure activities, spirituality / religiosity and the ability to separate the labor moments from those of their the personal lives, is advocated that such strategies do not offer significant resistance, since they do not question the contemporary legal-criminal logic. The thesis presented supports the proposals of penal abolitionism to present other conceptions of crime and justice through the invention of other practical and conceptual strategies.